Quantifying the Energy Security of Selected EU Countries - Obadi, Saleh Mothana; Korcek, Matej (International Journal of Energy Economics and Policy, 2020)
This paper examines the energy security of a selected group of EU countries. The study covers period 2006-2017 and is done for selected group of countries – Germany, France, Italy, Poland, Netherladns, United Kingdom and Slovakia. The primary used methodology is the z-score standardization. In order to obtain an index of greater complexity, we extended this methodology by incorporating Herfindahl-Hirschmann index (HHI) values for natural gas imports. Our findings suggest, that, among the largest energy consuming countries in the EU, Italy came as the country with the highest level of energy security index (ESI) as it benefitted from improved security of Supply. France ESI slightly decreased due to worsening indicator of economic availability. Poland and Slovakia both suffered from low advancements in the are of environmental acceptability. The complexity of the solved problem caueses undesired consequences, as development of ESI index deteriorated after German nulear phase-out. The paper clearly ducuments there there is not a single way how to approach enhancing a country’s energy security. Keywords: Energy security, EU, Z-score standardization, Herfindahl-Hirschmann index, natural gas JEL Classifications: Q40, Q42 DOI: https://doi.org/10.32479/ijeep.8847